A study on clinical significance of facial diagnosis and iris diagnosis in facial palsy: A case report - NARAYANASAMY, VIJAYARAGHAVAN; Ahalya, P G; Singh, C Pratap (Indian Journal of Case Reports, 2026)
According to the principles of naturopathy, disease is considered to arise from the accumulation of waste and toxic matter within the body, leading to impaired physiological functioning. Naturopathy emphasizes non-pharmacological interventions aimed at detoxification and restoration of normal bodily functions without adversely affecting vital organs. Facial palsy is one of the most common cranial nerve disorders and presents with characteristic facial asymmetry due to involvement of the facial nerve branches. It is commonly defined as an acute peripheral facial nerve palsy of unknown etiology, with many cases classified as idiopathic. This case report highlights the clinical significance of facial diagnosis and iridology as traditional natural diagnostic tools in the assessment of facial palsy. A 54-year-old male presented with reduced mobility of the left forehead and eyebrows, involuntary blinking of the left eye, facial pigmentation changes, and swelling of the jaw region. Facial diagnostic observations revealed asymmetry, altered facial expressions, and muscle weakness, while iridological examination showed nerve rings and lesions corresponding to facial and neurological regions. The findings suggest that facial diagnosis and iridology may serve as supportive, non-invasive assessment tools in the clinical evaluation of facial palsy.